Keterampilan Menulis Dongeng Menggunakan Metode Drill - Neneng Wahyuni (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2020)
The purpose of this study was to describe the skills of writing fairy tales using the drill method for seventh grade students of SMP Negeri 1, Guguak District, Lima Puluh Kota Regency. This research method uses quantitative methods with descriptive types. The results showed that the seventh grade students generally got an average score of 82.45 with a range of 76-85% with good qualifications. In conclusion, the skills of writing fairy tales using the drill method in the form of a student's fairy tale framework are classified as very good qualifications, the writing of the subject matter of fairy tales is in good qualifications and the writing of the sequence of story points is also classified as a good qualification. Keywords: Fairy Tale Writing Skills, Drill Method